A [COF-300]-[UiO-66] composite membrane with remarkably high permeability and H2/CO2 separation selectivity. Issue 21 (11th May 2018) - Das, Saikat; Ben, Teng
Abstract : A [COF-300]-[UiO-66] composite membrane has been fabricated that demonstrates phenomenally high permeability together with excellent H2 /CO2 separation selectivity. Abstract : In the last few years, the scientific community has capitalized on the synergy between different porous materials to develop mixed matrix- and composite membranes with unprecedented performance in gas separation. Admirably, several of these membranes have outperformed the trade-off between permeability and selectivity, and it is reasonable to suggest that these membranes owe their performance to the synergy between different porous materials that these membranes comprise. However, covalent–organic frameworks (COFs) are rather underexplored in the fabrication of composite membranes particularly due to the fabrication challenges. Herein, we report a continuous and uniform layer of COF-300 grown on a UiO-66 membrane to develop the [COF-300]-[UiO-66] composite membrane that exhibits outstandingly high permeability together with excellent H2 /CO2 separation selectivity.